Interdisciplinary trails in three southern Patagonian territories of the Butahuillimapu poetic (Revista LIDER, 2020)
This article proposes the hypothesis of textual identity construction in three southern Patagonian territories of the Butahuillimapu poetic, namely Benardo Colipán, Jaime Huenún and Clemente Riedemann. The identity geography reveals denied or closed areas that project, through their poetics, a way to exist. The presence of these areas in the poetic discourse interrogates the representation of geography and the difference of the territory that considers the social, cultural and political relations that converge in the process of identities construction.